Pengaruh Shift Kerja, Terapi Musik, dan Motivasi terhadap Beban Kerja Karyawan PT. TOA-GALVA Industries - Widiyarini Widiyarini (Jurnal Optimasi Sistem Industri, 2018)
TOA Corporation has a factory in Indonesia with name PT TOA Galva Industries producing technology of communication device. This research aims to make improvement towards the workload of the employees in the production of injection plastic part. Problems that arise due to the mental workload of employees affect concentration, performance, achievements, and motivation at work, quality of sleep at home, health, and work accident. This caused by the target measurement and checking of the products of the company are set, the deadline the measurement and checking of products, Division of working time/shift work, irregular work environment factors (noise, temperature, lighting, etc.), and the personal problems brought on when working. Using NASA-TLX (Task Load Index) can be measured the mental workload employees through the phase weighting and rating stage. Early research result obtained values of WWL (weighted workload) of morning shift employees is 76,78, afternoon shift 77,97 and night shift 80,0 results experienced high mental workload. Proposed improvements were made with improved shift work, the application of music therapy and motivation. The evaluation result of the implementation of the improvement suggests the value of WWL (weighted workload) of morning shift employee is 53,34, afternoon shift 54,43, night shift 55,45 result decrease mental workload.